Influences of the amino acids during alcoholic fermentation and development of aroma compounds in Sauvignon blanc - Serughetti, Alessandro (2018)
Mestrado Vinifera Euromaster - Instituto Superior de Agronomia - UL / Universitá degli Studi di Torino